Barriers in the development of the Malaysian brick industry / Wan Mohd Sabki Wan Omar, Che Sobry Abdullah and Umar Kassim - Wan Omar, Wan Mohd Sabki; Abdullah, Che Sobry; Kassim, Umar (2008)
Building materials form the largest input in construction, accounting for about 50 to 80 percent of the total value of construction, and bricks account an average of 15 percent of the material cost. It is the most widely used building material in Malaysia. It serves as the walling materials and plays a major role in the creation and renovation of a built environment. However, a reliable published data on the Malaysian brick industry seems to be not readily available. The aim of this paper is to examine the barriers of brick industry development in Malaysia. A total of 433 brick companies were surveyed of which 102 had responded. These respondents provided the data for the exploratory study, which was descriptive in nature. Of these 102 respondents, a total of 52 fired clay brick manufacturing companies were focused upon. This study revealed that most of the brick manufacturing companies can only be categorized as small sized enterprises. The results also indicated that the barriers in terms technology, energy, institutional, employees, and marketing have mild effect on the industry.